ICT-based geospatial decision support tool for fertilizer recommendation in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A prototype is being developed for testing in the growing season of 2021. This will also be linked with recommendation domains/similar response units to handle the complexity and spatial heterogeneity of Ethiopian landscapes and farms. The tool will be complemented with agro advisories to provide more integrated information for farmers.